An importance-performance analysis on selection attributes for young golf apparel consumers - Ji-hae Lee (Korea Institute of Sport Science, 2020)
Purpose The purpose of this study was to find out what young amateur golfers consider the most when purchasing golf apparel and to find out the Importance-Performance attributes when choosing golf apparel. Methods Amateur golfers in their 20s through 40s who have purchased golf clothing directly were selected as the subject. A total of 350 questionnaires were distributed using the purposive sampling method, and 331 copies as a final validity sample. For data analysis exploratory factor analysis Cronbach'α, frequency analysis, and Importance-Performance analysis by using SPSS 21.0. Results First, except for 'fancy design', 'water-proof function', 'elasticity comfort', 'brand name' there were significant differences between importance and satisfaction of selection attribute. Second, 'harmonic colors', 'has its own characteristics', 'expressing beauty', 'elasticity comfort' were analyzed to be situated in quadrant Ⅰ. Third, 'fancy design', 'water-proof function', 'temperature maintenance function', 'elasticity and durability', 'brand name', 'high-priced yet popular brand', 'popular brand' were analyzed to be situated in quadrant Ⅱ. Fourth, 'comfortable to wear', 'convenient for physical activity' were analyzed to be situated in quadrant Ⅲ. Fifth, 'can be also worn for outdoor wear', 'wear for gathering', 'wear as daily attire' were analyzed to be situated in quadrant Ⅳ. Conclusions The results will be the basis for effective target marketing on young amateur golfers who are rapidly emerging and will be able to grasp the characteristics of golf apparel that they really want.